PROPOSED MARKETING COMMUNICATION STRATEGY TO INCREASE PURCHASE INTENTION OF MANDALIKA TOUR DESTINATION IN ONLINE TRAVEL MARKETPLACE (The Indonesian Journal of Business Administration, 2021)
The growth of tourism industry has been rapidly increased proven by the increased amount of foreign tourist visit to Indonesia. Indonesian government recently prepares ten new tourist destination area called “10 Bali Baru”, including Mandalika as one of the priority tourist destination. PT HolaHalo is a new start up in online travel marketplace allowing travel agents and potential customers to meet and have transaction on tour destination packages. PT HolaHalo actively communicates Mandalika promotional video in its digital platform. However, the purchase of Mandalika tour package is still very low; and consumers and travel agents still do not trust to online travel market platform of PT HolaHalo. Hence, the objective of this research, to investigate the extent to which promotional video of PT HolaHalo could influence consumer positive response toward Mandalika tour package; to investigate significant factors that influence consumer intention to purchase Mandalika tour package; to develop marketing communication strategy to increase purchase intention. The researcher uses mix method of quantitative survey and qualitative interview in collecting internal and external data of PT HolaHalo. The external analysis of PESTEL, Five Porter Forces, and competitor analysis generates findings of opportunities and threats from external environment. Consumer analysis generates findings of significant factors that influence purchase intention, i.e. promotional video, trust toward PT HolaHalo, attractiveness of Mandalika, and consumer emotions. The internal analysis of STP, RBV, VRIO, Marketing mix generates findings of strengths and weaknesses of PT HolaHalo. Then the root causes of low purchase intention are identified, i.e. online travel marketplace business model of PT HolaHalo is easy to imitate; travel agents’ distrust to PT HolaHalo, video promotion do not arouse consumer positive emotions; consumer do not aware of PT HolaHalo; consumer distrust to PT HolaHalo, and HolaHalo do not utilize the attractiveness of Mandalika. This study generates alternative business solutions by conduction TOWS Matrix and Porter Business Strategic analysis. Then, five business solution is chosen by considering root cause of problem. Specifically, this study creates marketing communication strategy that is able to increase the purchase intention of Mandalika tour destination.Keywords: Tourism, Mandalika, online travel marketplace, marketing communication strategy